Barriers to Implementing the Code Blue System in Hospitals - Imtichan, Anis; Kosasih, Cecep Eli; Emaliyawati, Etika (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Introduction: The Blue Code system is one of the emergency procedure codes that should be activated immediately if a person is found and the condition of cardiac respiratory arrest. Success in the treatment of cardiac arrest depends on SDM, means and facilities that are supported by the code blue system.Purpose: The research is aimed at identifying barriers to the implementation of the Code Blue system in hospitals. The researchMethod: used is scoping review in documented using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), as well as PRISMA flow diagrams for detailed quantity of literature identified.Result: The research finds that there are still limitations in the implementation of the code blue system, which is an obstacle to the handling of code blue in hospitals.Conclusion: Based on the scopeing review research carried out, found obstacles to the implementation of the code blue system, including SDM both lack of SDM and which also contains team improvement in performing resuscitation starting from identification of patients with pulmonary heart failure, activation of code blue systems, response code blue team, implementation by the team, evaluation and documentation, means and insufficient prasarana, which in the end correlates in response team code blue in dealing with cardiac arrest.